Attempting to define the criteria for the urgent judiciary In Jordan: Comparative study - Alta’any, Mohammad Ali (Journal of Economic, Administrative and Legal Sciences, 2021)
Urgent judiciary means that the judge settles the disputes over which he fears the expiration of time quickly, if he does not prejudice the origin of the right, and this judiciary has its standards and conditions stipulated by law. Depending on the descriptive and analytical approach, this study aims to define the criteria for expedited judiciary as stipulated in Article (32) of the Code of Civil Procedure and the difference between these issues and urgent cases stipulated in Article (60) of the same law, It also seeks to clarify the general rules governing urgent matters and the judge’s authority to determine the issues that he feared from the expiration of time, since there is a difference between the adjudication of urgent matters and urgent cases, and it is necessary to examine this and not to confuse them, and also to stand on urgent issues and lawsuits that It is stipulated in comparative legislation, as well as the authority of the judge in determining issues that he fears the expiration of time. The study concluded that the Jordanian legislator was successful in his legislative approach, when he separated urgent matters and stipulated them in Article 32 of the Civil Procedures Law, while Article 60 of the same law was devoted to governing urgent cases. However, the legislator gave the judge absolute power to assess the matters that he fears from the expiration of time. Whereas, some judges consider some of the urgent matters to be feared over time, while another judge does not look at the same issue in the same way. The study recommended the necessity of finding legal questions to restrict this authority.
Keywords: urgent judiciary; civil procedures; urgent cases; Jordanian legislation